The Knowledge of Truth on the Basis of Transcendent Philosophy - Sayyid Muhammad tabatabai (حکمت اسرا, 2009)
The ‘Argument of the Sincere’ (burhÁn-e ÒiddÐqÐn), which is subsequent to essential contingency and the impossibility of an infinite regression, following on the groundwork of Avicenna, found its full blossoming in the school of Transcendent Philosophy—leaving in the process an indelible imprint on philosophical and theological works to come. While it is true that MullÁ HÁdÐ SabzawÁrÐ did not see the MullÁ ÑadrÁ’s explication of this Argument to be without defect, it was the novelty and ingenuity of ÝAllÁmah ÓabÁÔabÁÞÐ and ÀyatullÁh JawÁdÐ ÀmulÐ that made the special place of this explication among the other arguments for the existence of God fully known. The Argument of the Sincere is one of the most definitive and sublime of tawÎÐdÐ proofs whose middle term is none other than the Necessary Existent Itself. ÝAllÁmah ÓabÁÔabÁÞÐ’s succinct and exact exposition of the Argument, simply by the invalidation of sophistry, not only proves the existence of God but also His absolutely true unicity. The Argument in question here needs no preliminaries and is truly the first principle of philosophy as such. What is of import in this particular explication of the Argument is the fact that it is does not need any presuppositions whatsoever and that it suffices itself with a small series of preconceptions and presential certainties.